Efficiency of seed treatment against soil pytophagous on corn - Liaska, Y.; Strygun, A.; Kravchenko, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
Biological and technical effectivity of systemic insecticides (Kruizer 360 FS; Poncho 600 FS, TN; Gaucho Plus 466 FS, ТН; Fors Zea 280 FS) for corn grain protection from soil phytophagous was studied. Significant increasing of corn on grain yields was obtained during using of this drugs.